Berberine Slows the Progression of Prediabetes to Diabetes in Zucker Diabetic Fatty Rats by Enhancing Intestinal Secretion of Glucagon-Like Peptide-2 and Improving the Gut Microbiota - Wang, Ying; Liu, Haiyi; Zheng, Miaoyan; Yang, Yanhui; Ren, Huizhu; Kong, Yan; Wang, Shanshan; Wang, Jingyu; Jiang, Yingying; Yang, Juhong; Shan, Chunyan (Frontiers in Endocrinology, 2021)
Background: Berberine is a plant alkaloid that has multiple beneficial effects against intestine inflammation. In our previous study, we have found that berberine also possesses an antidiabetic effect. However, whether berberine is useful in the prevention of type 2 diabetes mellitus (T2DM) through its effect on intestine endocrine function and gut microbiota is unclear. Aim: To investigate the effects of berberine in the prevention of T2DM, as well as its effects on intestine GLP-2 secretion and gut microbiota in ZDF rats. Methods: Twenty Zucker Diabetic Fatty (ZDF) rats were fed a high-energy diet until they exhibited impaired glucose tolerance (IGT). The rats were then divided into two groups to receive berberine (100 mg/kg/d; berberine group) or vehicle (IGT group) by gavage for 3 weeks. Five Zucker Lean (ZL) rats were used as controls. Fasting blood glucose (FBG) was measured, an oral glucose tolerance test was performed, and the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) was calculated. Intestinal expression of TLR-4, NF-κB, TNF-α, mucin, zona occludens-1 (ZO-1) and occludin were assessed (immunohistochemistry). Plasma levels and glutamine-induced intestinal secretion of glucagon-like peptide-1 (GLP-1) and GLP-2 were measured (enzyme-linked immunosorbent assay). The plasma lipopolysaccharide (LPS) level was measured. Fecal DNA extraction, pyrosequencing, and bioinformatics analysis were performed. Results: After 3 weeks of intervention, diabetes developed in all rats in the IGT group, but only 30% of rats in the berberine group. Treatment with berberine was associated with reductions in food intake, FBG level, insulin resistance, and plasma LPS level, as well as increases in fasting plasma GLP-2 level and glutamine-induced intestinal GLP-2 secretion. Berberine could increase the goblet cell number and villi length, and also reverse the suppressed expressions of mucin, occludin, ZO-1 and the upregulated expressions of TLR-4, NF-κB and TNF-α induced in IGT rats(P<0.05). Berberine also improved the structure of the gut microbiota and restored species diversity. Conclusion: Berberine may slow the progression of prediabetes to T2DM in ZDF rats by improving GLP-2 secretion, intestinal permeability, and the structure of the gut microbiota.